2011
DOI: 10.1155/2011/830286
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformansas a Model for Radioimmunotherapy of Infections

Abstract: There is an obvious and urgent need for novel approaches to treat infectious diseases. The use of monoclonal antibodies in therapy of infectious diseases is now experiencing renewed interest. During the last 5 years radioimmunotherapy (RIT), a modality previously developed only for cancer treatment, has been successfully adapted for the treatment of experimental fungal, bacterial, and viral infections. As our model organism for studying the efficacy, mechanisms, potential toxicity, and radioresistance to RIT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…23 Significant improvement in AJ/Cr mouse survival was recorded when compared with control groups. [22][23][24] In addition, mAb 18B7 was also evaluated in a clinical trial in patients with C. neoformans infection. 22 Results showed that this mAb potentiates the antifungal activity of human and mouse effector cells, which activates the complement pathways leading to disposition of complement component 3 (C3) on the cryptococcal capsule.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…23 Significant improvement in AJ/Cr mouse survival was recorded when compared with control groups. [22][23][24] In addition, mAb 18B7 was also evaluated in a clinical trial in patients with C. neoformans infection. 22 Results showed that this mAb potentiates the antifungal activity of human and mouse effector cells, which activates the complement pathways leading to disposition of complement component 3 (C3) on the cryptococcal capsule.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…The effects of this therapy on bystander mammalian cells demonstrated minimal effects on host cells [151]. Reviews conducted to discuss the efficacy, toxicity, radiation resistance, radiobiological mechanisms and comparison with standard antifungal treatments [152] and the possibility of developing "panantibodies" for a universal treatment of the fungal diseases [148] suggest that this immunotherapeutic modality is a promising alternative for the treatment of invasive fungal infections.…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…Cryptococcus spp. are environmental fungal pathogens afflicting immunocompromised patients as well as immunocompetent individuals, causing life-threatening meningoencephalitis ( Idnurm et al, 2005 ; Jarvis et al, 2008 ; Dadachova and Casadevall, 2011 ; Del Poeta and Casadevall, 2011 ; Kronstad et al, 2011 ; Kozubowski and Heitman, 2012 ). Cryptococcus causes approximately one million annual cases of meningoencephalitis globally among AIDS patients, leading to nearly 625,000 deaths ( Park et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%